Perbandingan Kemampuan Pemecahan Masalah Matematika Menggunakan Model PBL dan Discovery Learning - Lestari, Yuyun; Arifmiboy, Arifmiboy; Malta, Malta (Universitas PGRI Madiun, 2023)
This research was motivated by the lack of ability to solve problems and the students were less able to think creatively, be active in the learning process. aims to describe the comparison of mathematical problem solving abilities using the PBL Model with Discovery Learning. This type of research uses factorial design. The sampling technique is probability sampling with proportionate stratified random sampling. The samples in this study were the experimental group I class V SD Negeri 11 Koto Salak using the PBL model and the experimental group II class V SD Negeri 08 Koto Salak using the Discovery Learning model, totaling 16 and 15 students respectively. The research instruments are description tests and questionnaires. The data analysis technique used is the T-test and two-way ANOVA through the normality test and homogeneity test. Based on the research results, problem solving abilities were tested and processed using the T-Test and Two-Way Anova. The results of calculating the differences in students' problem solving abilities using the PBL model with the Discovery Learning model obtained significant results 5. Based on the hypothesis results obtained significant results of 0.000, which means the results sig(0.000) <0.05. The Ha hypothesis is accepted if sig<0.05 and the Ho hypothesis is accepted if sig>0.05. Based on the results of the sig hypothesis Ha is accepted, meaning that there are differences in students' problem-solving abilities in learning mathematics using the PBL model with Discovery Learning. regardless of the child's initial abilities. So, it can be concluded that there is a significant difference in the ability to solve problems using the PBL model with the Discovery Learning model for Class V Elementary Schools.